Clique And Path Non Split Domination Of G_n- Graph (Journal of Namibian Studies : History Politics Culture, 2023)
An undirected graph  defined on a finite subset of natural numbers, is an undirected graph whose vertex set  and  are adjacent if and only if . In this paper, Clique domination and Path non-split domination is discussed and the some results are presented at various values of   of gn